P–773 Infertility treatment and the risk of small for gestational age births: a population-based study in the United States. (6th August 2021) - Glatthorn, H; Sauer, M; Brandt, J; Ananth, C
Abstract: Study question: What is the association between infertility treatments and small for gestational age (SGA) births? Summary answer: Women who conceived pregnancies with any infertility treatment had a decreased risk of SGA <10th, <5th and <3rd percentiles compared to naturally conceived pregnancies. What is known already: Assisted reproductive technology (ART) and other infertility treatments have long been associated with an increased risk of SGA births, which confers a greater risk of perinatal morbidity and mortality compared to appropriate for gestational age births. Study design, size, duration: This is a cross-sectional study of 16, 836, 228 births in the United States (US) between 2015–2019. The exposure group included women who underwent any infertility treatment, including ART and prescribed fertility enhancing medications. The comparison group included those who had naturally conceived pregnancies. The primary outcome was SGA birth, defined as sex-specific birthweight <10th percentile for gestational age. Secondary outcomes included SGA <5th and <3rd percentile births. Participants/materials, setting, methods: Pregnant subjects (n = 16, 836, 228) in the US who delivered non-malformed, singleton live births between 24–44 weeks' gestational age. We estimated risk of SGA births in relation to any infertility treatment from fitting log-linear Poisson regression models with robust variance. Risk ratios (RR) and 95% confidence intervals (CI) were estimated as the effect measure before and after adjusting for confounders. We also performed a sensitivity analysis to correct for potential non-differential exposure misclassification and unmeasured confounding biases. Main results and the role of chance: During the study period, 1.4% (n = 231, 177) of non-malformed singleton live births resulted from infertility treatments (0.8% ART and 0.6% fertility enhancing medications). Of these, 9.4% (n = 21, 771) of pregnancies conceived with infertility treatment were complicated by SGA <10th percentile compared to 11.9% (n = 1, 755, 925) of naturally conceived pregnancies. For pregnancies conceived with infertility treatment versus naturally conceived pregnancies, the adjusted RR for SGA <10th percentile was 1.07 (95% CI 1.06, 1.08). However, after correction for misclassification bias and unmeasured confounding, infertility treatment was found to be protective for SGA and conferred a 27% reduced risk of SGA <10th percentile (bias-corrected RR 0.73, 95% CI 0.53, 0.85). These trends were similar for analyses stratified by exposure to ART and fertility enhancing medications and secondary SGA outcomes, including SGA <5th and <3rd percentile. Limitations, reasons for caution: All information collected on infertility treatment relies on self-reporting by patients and recording by hospital staff at the time of delivery, which likely resulted in underreporting of infertility treatments. Additionally, we cannot determine the impact of interventions that were not recorded, such as intrauterine insemination (IUI). Wider implications of the findings: Compared to naturally conceived pregnancies, exposure to infertility treatment is associated with reduction in the risk of SGA births. These findings, which are contrary to some published reports, likely reflect changes in the modern practice of infertility care in the US, and importantly, robust analysis of the national data. Trial registration number: Not applicable